Hubungan BMI dan Lemak Tubuh pada VO₂Max Kapasitas Mahasiswa Pendidikan Jasmani Universitas Mulawarman - Gyta Krisdiana Cahyaningrum; Naheria Naheria; Didik Cahyono; Muhammad Sukron Fauzi; Muchamad Samsul Huda (Universitas Nusantara PGRI Kediri, 2025)
This study examines the relationship between Body Mass Index (BMI), body fat proportion, and VO₂Max capacity in Physical Education students enrolled in 2022 at FKIP Mulawarman University. The research method used a cross-sectional design. The sample amounted to 80 students through random sampling (53 males and 27 females) aged 18–22 years. BMI was calculated from weight and height using a digital scale and stadiometer, body fat proportion was measured using skinfold callipers at three points (triceps, abdomen, thighs), and VO₂Max capacity was measured with the multistage fitness test (beep test). Data analysis employed SPSS 25.0, using descriptive statistics to present the distribution of BMI, body fat proportion, VO₂Max, and Pearson product-moment correlation to assess the strength and direction of relationships between variables. The findings show a significant relationship between BMI and VO₂Max (r = -0.45, p < 0.01), while the relationship between body fat proportion and VO₂Max is stronger (r = -0.52, p < 0.01). It can be concluded that body fat proportion is a more influential factor than BMI in determining VO₂Max capacity. These results contribute to the understanding that body composition, particularly fat proportion, plays a crucial role in aerobic capacity. The contribution of this study lies in providing empirical evidence to support the development of exercise programs and curricula based on physiological profiles, which can be adapted to other educational contexts.